Phonological Processing, Reading Speed, Accuracy, and Reading Comprehension in Children with ASD, Epilepsy, and Comorbidity - Porcar-Gonzalbo, Nadia (2026)
Objective. This study compared performance in phonological processing, reading speed, reading accuracy, and reading comprehension in 170 children aged 7 to 9 years with diagnoses of autism spectrum disorder (ASD), epilepsy, or comorbid ASD and epilepsy. Method. The PROLEXIA and PROLEC-R batteries were used as assessment instruments. Data were analyzed using MANOVA to examine differences between groups. Results. The results showed that children with comorbid ASD and epilepsy exhibited lower performance in all assessed areas compared to children with ASD only or epilepsy only, indicating poorer reading-related skills in participants with a comorbid diagnosis of ASD and epilepsy.